Evaluation of the nutritional composition of maca and cañihua, from various departments of Peru - Blanco Blasco, Teresa (2022)
The following study is for living knowledge about the chemical and nutritional content of maca and cañihua coming of the principal areas of production in our country, and for diffuseness of its nutritional value inside the population contributing to improve the level and quality of life of Peruvians.For this we took 25 samples of maca from the soils of Junín, Puno, Ancash y Cerro de Paseo. They were obtained at random from the cultivated fields. The circunstances of this work was when the crop of this species was carried out and taken to the regional markets.We proceed to the determination of the protein content by the method of Microkjeldhal, aminoacids content by liquid chromatography of high performance, fat, carbohydrates, ash, fiber, humidity determination according to Peruvian Thecnical norms and determination of mineral by spectrophotometric in atomic absortion.We obtained as conclusion that the samples of maca of different Departments of Peru, have different values of protein, and the best of them was from Cerro de Paseo with an average of 9,73 g/100g of food. The fat content as the aminoacids, lysine, valine, threonine, leucine, isoleucine and arginine content were good in maca of Cerro de Paseo. The values of magnesium, iron and cooper were proper.The studies of cañihua from Junin, Ayacucho, Cusco and Puno demonstrated good values of pro teins with averages between 13 and 14 g/100g of food, specia1ly from Ayacucho. The fat concentration was better in cañihua from Ayacucho and Junin than in that from Cusco y Puno. The same was with de aminoacids investigated. The values of magnesium of all the samples were very elevated, about 157 to 223 mg/100g of food, for cooper were 0,68 to 1,30 mg/100g of food. The studies of iron in cañihua showed us that the samples of Ayacucho and Cusco had 18,10 and 21,17 mg/100g of food, and it was the quarter of the 81,79 and 60,91 mg/100g of food we obtained with cañihua from Junin and Puno.We concluded that maca of Cerro de Paseo and the cañihua from Ayacucho are the most nutritive in Perú.